1997
DOI: 10.1111/j.1469-7610.1997.tb01620.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention in Adoptive Families: Supporting Maternal Sensitive Responsiveness, Infant–Mother Attachment, and Infant Competence

Abstract: Results from adoption studies suggest that adoptive families may experience special impediments with respect to the developmental progress and outcome of their children. Based on attachment theory, two early intervention programs were designed to support families in the Netherlands with an internationally adopted child. The intervention aimed at promoting maternal sensitive responsiveness, secure infant-mother attachment relationships, and infant exploratory competence. Ninety families with an interracially ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
7

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 36 publications
3
85
0
7
Order By: Relevance
“…They were requested to participate in a study examining the development of adopted children. The results of the intervention study were reported elsewhere (Juffer, Hoksbergen, Riksen-Walraven, & Kohnstamm, 1997 ;Stams, Juffer, Van IJzendoorn, & Hoksbergen, in press). The intervention was not repeated during the following years.…”
Section: Methods Participantsmentioning
confidence: 99%
“…They were requested to participate in a study examining the development of adopted children. The results of the intervention study were reported elsewhere (Juffer, Hoksbergen, Riksen-Walraven, & Kohnstamm, 1997 ;Stams, Juffer, Van IJzendoorn, & Hoksbergen, in press). The intervention was not repeated during the following years.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Similarly, three articles (Juffer et al, 1997(Juffer et al, , 2005Stams et al, 2001) were found to be follow-ups of the same sample and are therefore also considered here as one study. In total, ten studies (13 articles) were included in the review.…”
Section: Database Searchesmentioning
confidence: 99%
“…The adoptive parents might have difficulty attaching to an older child, who may be traumatised, sad or angry. The adoptive parents might also interfere with a normal attachment process due to their own specific traumas, grief and inabilities to attach [28][29][30][31][32]50]. This is a difficult situation and can require professional help to resolve, and is a reason why adoptive parents are now included in the search for criteria affecting the attachment process.…”
Section: Think I Am Familymentioning
confidence: 99%
“…The importance of age on arrival has been demonstrated [28,51,52]; whereas others have found that the most influential factor is not age on arrival, but the parents ability to invest emotionally in their child [53]. By measuring "maternal sensitivity", i.e.…”
Section: Think I Am Familymentioning
confidence: 99%
See 1 more Smart Citation